Synthesis of 2′-O-methyl-RNAs incorporating a 3-deazaguanine, and UV melting and computational studies on its hybridization properties - Seio, Kohji (Oxford University Press, 2006)
2′-O-Methyl-RNAs incorporating 3-deazaguanine (c(3)G) were synthesized by use of N,N-diphenylcarbamoyl and N,N-dimethylaminomethylene as its base protecting groups to suppress sheared-type 5′-GA-3′/5′-GA-3′ tandem mismatched base pairing which requires the N(3) atom. These modified RNAs hybridized more weakly with the complementary and single mismatch-containing RNAs than the unmodified RNAs. The T(m) experiments were performed to clarify the effects of replacement of the fifth G with c(3)G on stabilization of 2′-O-methyl-(5′-CGGCGAGGAG-3′)/5′-CUCCGAGCCG-3′ and 2′-O-methyl-(5′-CGGGGACGAG-3′)/5′-CUCGGACCCG-3′duplexes, which form sheared-type and face-to-face type 5′-GA-3′/5′-GA-3′ tandem mismatched base pairs, respectively. Consequently, this replacement led to more pronounced destabilization of the former duplex that needs the N(3) atom for the sheared-type base pair than the latter that does not need it for the face-to-face type base pair. A similar tendency was observed for 2′-O-methyl-RNA/DNA duplexes. These results suggest that the N(3) atom of G plays an important role in stabilization of the canonical G/C base pair as well as the base discrimination and its loss suppressed formation of the undesired sheared-type mismatched base pair. Computational studies based on ab initio calculations suggest that the weaker hydrogen bonding ability and larger dipole moment of c(3)G can be the origin of the lower T(m).